2018
DOI: 10.1103/physreva.97.012125
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-variable quantum probes for structured environments

Abstract: We address parameter estimation for complex/structured systems and suggest an effective estimation scheme based on continuous-variables quantum probes. In particular, we investigate the use of a single bosonic mode as a probe for Ohmic reservoirs, and obtain the ultimate quantum limits to the precise estimation of their cutoff frequency. We assume the probe prepared in a Gaussian state and determine the optimal working regime, i.e. the conditions for the maximization of the quantum Fisher information in terms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 58 publications
2
47
3
Order By: Relevance
“…[51]), or even structured environments (e.g., see Ref. [52]) to be studied in the near future. = iA â †2 e iθs −â 2 e −iθs + 2iA β cosh re −iθs − β * sinh r â + β sinh r − β * e iθs cosh r â † + iA(β * 2 e iθs − β 2 e −iθs ), where β = |β| e iθb , and assuming that r 0, it can easily be shown that when A = (2n th + 1) sinh 2r 2n 2 th + 2n th + 1 , |β| = |α| A(2n th + 1)…”
Section: Discussionmentioning
confidence: 99%
“…[51]), or even structured environments (e.g., see Ref. [52]) to be studied in the near future. = iA â †2 e iθs −â 2 e −iθs + 2iA β cosh re −iθs − β * sinh r â + β sinh r − β * e iθs cosh r â † + iA(β * 2 e iθs − β 2 e −iθs ), where β = |β| e iθb , and assuming that r 0, it can easily be shown that when A = (2n th + 1) sinh 2r 2n 2 th + 2n th + 1 , |β| = |α| A(2n th + 1)…”
Section: Discussionmentioning
confidence: 99%
“…Under certain regularity assumptions, the QFI matrix encodes the ultimate precision bounds on the estimation of unknown parameters encoded in a density matrix (know as quantum Cramer-Rao bounds), while the SLDs and their commutators determine whether such bounds may be saturated with physically realizable measurements [5,6]. The associated applications are plenty, including phase and frequency estimation [4,[7][8][9][10][11][12][13][14][15][16][17], estimation of noise parameters [18][19][20][21][22][23], joint estimation of unitary and/or noisy parameters [24][25][26][27][28][29][30][31], sub-wavelength resolution of optical sources [32][33][34][35][36][37][38], nano-scale thermometry [39][40][41][42][43][44][45], and estimation of Hamiltonian parameters in the presence of phase-transitions [46][47][48]. The most common approach for ...…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, technological advances in control and manipulation of quantum systems have made quantum probes available to the characterization of a large set of physical platforms. In turn, a radically new approach to probe complex quantum systems emerged, and it is based on the quantification and optimization of the information that can be extracted by an immersed quantum probe, as opposed to a classical one [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Quantum probes offer two main advantages: on one hand, they often provide enhanced precision, due to the inherent sensitivity of quantum system to environment-induced decoherence.…”
Section: Introductionmentioning
confidence: 99%